2023
DOI: 10.3390/life13030643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Humidity on Soil Gross Nitrogen Transformation in a Typical Shrub Ecosystem in Yanshan Mountain and Hilly Region

Abstract: Shrubland is a pivotal terrestrial ecosystem in China. Soil nitrogen transformations play a crucial role in maintaining the productivity of this ecosystem, yet the driving forces underlying it have not been sufficiently addressed, particularly under ongoing climate changes. Herein, by incorporating 15N isotope pool dilution method in laboratory incubation, the rates of gross N ammonification, nitrification, and inorganic N consumption in soils in response to varying temperature and humidity conditions were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…Research shows that lowering sewage temperatures helps reduce the number of bacteria and archaea. Similar dependencies were obtained for soil, where humidity and temperature affect the rate of ammonification and nitrification [9,10]. Previous research indicates that ammonia-oxidizing bacteria (AOB) dominate in the soil at low temperatures, and ammonia-oxidizing archaea (AOA) dominate at high temperatures [11].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Research shows that lowering sewage temperatures helps reduce the number of bacteria and archaea. Similar dependencies were obtained for soil, where humidity and temperature affect the rate of ammonification and nitrification [9,10]. Previous research indicates that ammonia-oxidizing bacteria (AOB) dominate in the soil at low temperatures, and ammonia-oxidizing archaea (AOA) dominate at high temperatures [11].…”
Section: Introductionsupporting
confidence: 71%
“…Mechanically pre-treated sewage gravitationally flows through the separation chamber to the averaging tank (3) from where it is pumped further to two biological reactors of the SBR type (4.1) and (4.2). The phases of reactor operation, aerobic and anaerobic conditions, and filling and decanting of sewage are shown later in the workBiological phosphorus removal is supported using a PIX coagulant dosed into SBR reactors from the PIX dosing station (9). In addition, sludge management is conducted.…”
Section: Place Of Researchmentioning
confidence: 99%
“…Previous studies by MacDonald et al [36] also found that the rate of microbial respiration and the mineralization of nitrogen waste degradation are temperature-dependent. In Hu et al [37], it is further highlighted how moisture variation impacts microbial activities, oxygen concentration, and nutrient transport. Excessive moisture potentially leads to nitrogen loss via denitrification and impeding BSF larval growth.…”
Section: Effect Of Environmental Factors On Nitrogen Accumulation In ...mentioning
confidence: 99%
“…This makes the impact of climate warming more pronounced in these areas. Research has determined that temperature and humidity are key factors influencing the mineralization of different types of soil N [37,38], with temperature playing a more prominent role [39]. In general, an increase in soil temperature facilitates the N cycle in the soil [40,41], while a reduction in soil moisture content impedes this process [42].…”
Section: Introductionmentioning
confidence: 99%